2011
DOI: 10.1007/s10620-011-1789-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Glycyrrhizin in the Early Stage of Acute Onset Autoimmune Hepatitis

Abstract: The early introduction of sufficient doses of SNMC might prevent disease progression in patients with acute onset AIH. SNMC can be used safely and be useful for patients with difficult-to-diagnose acute liver disease as an 'initial' treatment tool to improve liver inflammation before starting disease-specific treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…Several clinical studies reported that GA was efficacious in the treatment of various types of inflammation (mainly in liver [21][22][23][24][25][26][27][28][29][30] (Table 1), but also in lung, kidney, intestine, and spinal cord [31]). The most common use of GA is in the treatment of liver disease [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies reported that GA was efficacious in the treatment of various types of inflammation (mainly in liver [21][22][23][24][25][26][27][28][29][30] (Table 1), but also in lung, kidney, intestine, and spinal cord [31]). The most common use of GA is in the treatment of liver disease [32].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical validation of the efficacy of intravenous glycyrrhizin in liver injury has been explored in a randomized controlled trial of chronic HCV, where it was administered chronically and shown to significantly reduce serum ALT, but not HCV RNA levels [16]. More recently, intravenous glycyrrhizin has been shown to promote transaminase normalization in patients with acute autoimmune hepatitis though this prospective study did not have a steroid alone comparator arm to compare to the standard of care therapy [17]. Anti-HMGB1 blocking antibodies have been shown to protect from acetaminophen and concanvalin-induced acute liver injury, but have not been tested in humans [18] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our present results demonstrated the protective effects of RKT against BLM-induced ALI in mice. In regard to safety and tolerability, RKT, hesperidin, and glycyrrhizin administrations each had no severe side effects (21,28,45,46,59). We thus believe that RKT could provide a hopeful therapeutic strategy for ALI/ARDS.…”
Section: Discussionmentioning
confidence: 81%